Migrants as agents of change : social remittances in an enlarged European Union - Grabowska, Izabela; Garapich, Michał P.; Jażwińska-Motylska, Ewa; Radziwinowiczówna, Agnieszka (Migration, diasporas and citizenship., 2017)
"An important contribution to debates about migration and social change. Based on interdisciplinary, longitudinal research on migration between three Polish communities and the United Kingdom in post-accession Europe, Grabowska and her colleagues carefully unpack how social remittance transfers actually work. In a world in which sending governments look increasingly to emigrants' economic and social contributions, this book is an invaluable guide to how and when innovation, or resistance to it, occur."--Peggy Levitt, Wellesley College and Harvard University, USA This book offers a unique and innovative way of looking at the paradoxical consequences of human mobility. Based on a three-year transnational multi-sited longitudinal research project, it demonstrates that not all migrants acquire, transfer and implement social remittances in the same way. Whilst the circulation of ideas, norms and practices is an important aspect of modernity, acts of resistance, imitation and innovation mean that whilst some migrants become ordinary agents of social change in their local microcosms, others may contest that change. By putting this individual agency centre stage, the authors trace how social remittances are evolving, and the ambiguous impact that they have on society. This thought-provoking work will appeal to students and scholars of sociology, geography and anthropology.